2021
DOI: 10.1152/japplphysiol.00630.2020
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in vascular function in response to acute lower limb heating in young healthy males and females

Abstract: Regular exposure to passive heat stress improves vascular function, but the optimal heating prescription remains undefined. Local limb heating is more feasible than whole body heating, but the evidence demonstrating its efficacy is lacking. The purpose of this study was to determine whether acute improvements in vascular function can be achieved with lower limb heating in 16 young healthy individuals (8 female, 8 male). In separate visits, participants underwent 45-min of ankle- and knee-level hot water immers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 58 publications
4
22
0
Order By: Relevance
“…The present findings of local stiffness are in agreement with past whole body and two leg hyperthermia studies which reported no changes in regional (carotid-radial) arterial stiffness (Ganio et al, 2011;Moyen et al, 2016;Schlader et al, 2019). However, studies exploring the recovery following hyperthermia, reported decreases in peripheral and/ or leg (femoral-ankle region) arterial stiffness alongside an elevated core temperature (Caldwell et al, 2017;Cheng et al, 2021;Lee et al, 2018;Sugawara & Tomoto, 2021;Thomas et al, 2017). The latter observations contrast with the unaffected or small changes in arterial stiffness/distensibility, core temperature, and arterial pressure observed in the present and previous single leg heating studies (Chiesa et al, 2015(Chiesa et al, , 2016Engelland et al, 2020;Takahashi et al, 2011).…”
Section: Hyperthermia Influence On Local Arterial Distensibilitysupporting
confidence: 91%
“…The present findings of local stiffness are in agreement with past whole body and two leg hyperthermia studies which reported no changes in regional (carotid-radial) arterial stiffness (Ganio et al, 2011;Moyen et al, 2016;Schlader et al, 2019). However, studies exploring the recovery following hyperthermia, reported decreases in peripheral and/ or leg (femoral-ankle region) arterial stiffness alongside an elevated core temperature (Caldwell et al, 2017;Cheng et al, 2021;Lee et al, 2018;Sugawara & Tomoto, 2021;Thomas et al, 2017). The latter observations contrast with the unaffected or small changes in arterial stiffness/distensibility, core temperature, and arterial pressure observed in the present and previous single leg heating studies (Chiesa et al, 2015(Chiesa et al, , 2016Engelland et al, 2020;Takahashi et al, 2011).…”
Section: Hyperthermia Influence On Local Arterial Distensibilitysupporting
confidence: 91%
“…The sample size calculation (a priori) was based on data from the study by Brunt et al (2016), which observed a 2.5% increase in brachial artery FMD following 8 weeks of wholebody bathing, and based on these data, a minimum of 13 participants per group was required in order to reject the null hypothesis with 80% power (p<0.05). However, as the present study tested the acute effects of ankle bathing, the sample size was re-calculated (post hoc) using data from the study by Cheng et al (2021), which observed an 0.8% increase in brachial artery FMD following an acute bout of 45 min of lower limb heating in young adults (4.6%±1.7% versus post: 5.4%±2.0%) with medium-sized effects (Cohen's d= 0.43). A total sample size of 42 participants had enough statistical power (82%) to test a 3x3 ANOVA with repeated measures with the effect size (f value) using a medium-sized partial η 2 (0.05) (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…HSP is known to improve nitric oxide signaling and reduce oxidative stress and inflammation (Pritchard et al 2001;Suzuki et al 2002). Indeed, acute knee-level bathing has been shown to increase plasma concentrations of extracellular HSP-72 and improve brachial artery FMD (Cheng et al 2021). Thus, these previous studies have highlighted the beneficial effects of acute thermal therapy on vascular function.…”
Section: Brachial Artery Flow-mediated Dilationmentioning
confidence: 99%
See 2 more Smart Citations